2018
DOI: 10.1002/elan.201800623
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Electrochemical Sensors Based on Molecularly Imprinted Polymers and Nanomaterials

Abstract: This review focuses on the recent achievement during period of 2013–2018 related to the electrochemical sensors based on molecularly imprinted polymers (MIPs) combined with nanomaterials for various kinds of applications. MIPs based electrochemical sensors have found a great interest due to their high stability, short time required for electropolymerization, and high specificity towards the target analyte. The sensitivity is considered as one of the important parameter in electrochemical sensing strategies tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(67 citation statements)
references
References 143 publications
0
65
0
2
Order By: Relevance
“…Molecular imprinting technique is also the substitute of natural receptors and successfully used as an articial analytical receptor for molecular identication with binding properties as natural antibodies in immunoassays. 10,11 Therefore, MIPs are termed as plastic anti-bodies. Literature reveals that including biological structure more than 10 000 molecules such as inorganic ions, drugs, cells, nucleic acid, protein, and viruses have been imprinted successfully.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular imprinting technique is also the substitute of natural receptors and successfully used as an articial analytical receptor for molecular identication with binding properties as natural antibodies in immunoassays. 10,11 Therefore, MIPs are termed as plastic anti-bodies. Literature reveals that including biological structure more than 10 000 molecules such as inorganic ions, drugs, cells, nucleic acid, protein, and viruses have been imprinted successfully.…”
Section: Introductionmentioning
confidence: 99%
“…When MIP-NP binds to the target analyte, the transducer will produce electrical signal depend on the concentration or number of target analytes that are bind to MIP-NP. Then, the signal was measured by the signal processor electrochemically, either through voltammetry, amperometry, potentiometry, or impedance [14,[36][37][38].…”
Section: Mip-nps In Electrochemical Sensorsmentioning
confidence: 99%
“…Several related reviews have been reported. Lahcen et al [10] mainly presented the development of MIPs modified with nanomaterials for electrochemical biosensors. Good electrical catalytic properties and excellent conductivity of nanomaterials combined with the comparable selectivity of MIPs endow them with powerful performance for various kinds of biomarkers.…”
Section: Introductionmentioning
confidence: 99%